Correlation between radiographic and pathologic lymph node involvement and extranodal extension via CT and PET in HPV-associated oropharyngeal cancer. (December 2021) - Kowalchuk, Roman O.; Van Abel, Kathryn M.; Yin, Linda X.; Garcia, Joaquin; Harmsen, William S.; Moore, Eric J.; Price, Daniel L.; Chintakuntlawar, Ashish V.; Price, Katharine R.; Lester, Scott C.; Neben Wittich, Michelle; Patel, Samir H.; et al.
Highlights: CT and PET/CT had low sensitivity and specificity for pathologic extranodal extension. CT and PET/CT had high specificity (> 90%) for identifying > 4 pathologic lymph nodes. > 90% of patients with ≤ 4 radiographically involved nodes remained N1 after surgery. Abstract: Purpose/Objectives: Extranodal extension (ENE) and more than 4 pathologically involved lymph nodes (pN2) are critical prognostic factors in HPV-associated oropharyngeal cancer (HPV(+) OPSCC). We analyze a patient cohort with HPV(+) OPSCC to determine the sensitivity and specificity of CT and PET/CT in identifying involvement of more than 4 lymph nodes (rN2) compared to pN2 and radiographic ENE (rENE) compared to pathologic ENE (pENE). Materials/Methods: The dataset consisted of 261 patients enrolled in two prospective clinical trials. All imaging studies were independently reviewed by a blinded neuroradiologist, classifying the presence or absence of rENE and rN2. Secondary analyses included correlations of imaging accuracy and pathologic size of the primary tumor. Results: CT demonstrated sensitivity of 59%, specificity of 92%, positive predictive value (PPV) of 53%, negative predictive value (NPV) of 94%, and accuracy of 88% for pN2. PET/CT showed similar results. Patients with up to 4 involved lymph nodes (rN0-1) had a 93–94% chance of remaining pN0-1. CT and PET/CT identified an equal number of involved nodes in 81% of patients. CT demonstrated sensitivity of 54%, specificity of 71%, PPV of 72%, NPV of 53%, and accuracy of 62% for pENE. PET/CT showed similar outcomes. Notably, when multiple radiographic criteria were used to identify rENE, PPV increased for both CT (84%) and PET/CT (79%). Conclusion: Patients with rN0-1 had a 93–94% chance of remaining pN0-1, suggesting rN0-1 could effectively stratify patients for clinical trials and treatment de-escalation. While CT and PET/CT were highly correlated, both showed low sensitivity for identifying pENE.